2022
DOI: 10.3390/ijerph19159019
|View full text |Cite
|
Sign up to set email alerts
|

Association between Recreational Screen Time and Sleep Quality among Adolescents during the Third Wave of the COVID-19 Pandemic in Canada

Abstract: The study objective was to verify whether recreational screen time was associated with sleep quality among adolescents during the third wave of the COVID-19 pandemic in Canada. Data collection took place in four high schools in the region of Chaudière-Appalaches (Quebec, Canada) from the end of April to mid-May 2021. Recreational screen time and sleep quality were measured using the French versions of validated questionnaires specifically designed for adolescents. A total of 258 adolescents (14–18 years; 66.3%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 48 publications
3
12
0
Order By: Relevance
“…Boys had a higher recreational screen time compared with girls (7 h and 34 min/day vs. 5 h/day, p < 0.0001). Differences in recreational screen time between boys and girls are detailed elsewhere [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Boys had a higher recreational screen time compared with girls (7 h and 34 min/day vs. 5 h/day, p < 0.0001). Differences in recreational screen time between boys and girls are detailed elsewhere [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was measured using a French version of the validated short version of the Adolescent Sleep–Wake Scale [ 33 , 34 ], which was translated by a certified translator. The results on the association between adolescents’ sleep quality and recreational screen time are already published [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, sleep problems in adolescents during the pandemic have also been frequently associated with specific daily habits. Specifically, longer screen time [ 135 , 136 , 147 , 148 , 149 , 150 , 151 , 152 , 153 ] and lower physical activity [ 149 , 154 ] have been associated with different measures of poor sleep quality. Considering the influence of these variables on sleep habits in adolescents [ 14 , 155 , 156 , 157 ], these findings are consistent with the increased screen time and sedentary behaviors observed in youth during the pandemic [ 119 , 120 , 121 , 122 , 141 ].…”
Section: The Impact Of Covid-19 Outbreak On Sleep and Mental Health I...mentioning
confidence: 99%
“…[10][11][12] Currently, in China, the impact of digital screens on myopia in children and adolescents has garnered attention [13][14][15] and the increased exposure to digital screens has aggravated other ocular surface and psychological issues, such as DE and insomnia. [3,[16][17][18] Recent studies have reported that DED symptoms often accompany systemic comorbidities such as migraine, chronic pelvic pain, musculoskeletal pain, chronic pain conditions, irritable bowel syndrome, insomnia symptoms, and low quality of life. , [8,9,11,12] Both DED and sleep disorders have been implicated in reducing the quality of life, and recent studies have pointed to a possible relationship between sleep disturbance associated with circadian rhythm disruption and even hypertension and metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…, [8,9,11,12] Both DED and sleep disorders have been implicated in reducing the quality of life, and recent studies have pointed to a possible relationship between sleep disturbance associated with circadian rhythm disruption and even hypertension and metabolic syndrome. [17][18][19][20] It has been reported that tear secretion and tear stability have a circadian rhythm [21,22] and tear secretion system might be associated with the renin-angiotensin system, [23] as metabolic syndrome patients have lower tear secretion. [20] We conducted the present study to explore the relationship between poor sleep quality and DED.…”
Section: Introductionmentioning
confidence: 99%